Tribological characterization of microarc oxidized alumina coatings for biological applications - Baxi, Juhi; Kar, Presenjit; Liang, Hong; Polat, Aytekin; Usta, Metin; Ucisik, Ahmet Hikmet (Pergamon-Elsevier Science Ltd, 2008)
Coatings with high wear and corrosion resistance are desirable in tribological and biological applications. In an attempt to develop such coatings, we used microarc oxidation (MAO) method to generate noble coatings of alumina on aluminum alloys. This paper reports our tribological investigations on these coatings with a pin-on-disk tribometer in synthetic biofluid. The frictional behavior and wear mechanisms were studied through surface characterization using a scanning electron microscope and a surface profilometer. It was found that the MAO coatings were highly wear resistant in the biofluid environment. The frictional behavior depends on the relative hardness of the ball-on-disk materials. The increased alpha-Al2O3 and gamma-Al2O3 phases with an increase in the current intensity were found to reduce the friction. (C) 2008 Elsevier Ltd. All rights reserved.
6th International Symposium on Applied Plasma Science -- SEP 24-28, 2007 -- Nikko, JAPAN
Keywords: Microarc oxidation (MAO); Alumina coatings; Artificial joints